2002
DOI: 10.1115/1.1457453
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of Cavitating Flow in Centrifugal Pumps Using Multiphase CFD

Abstract: A multi-phase CFD method is used to analyze centrifugal pump performance under developed cavitating conditions. The differential model employed is the homogeneous two-phase Reynolds-Averaged-Navier-Stokes equations, wherein mixture momentum and volume continuity equations are solved along with vapor volume fraction continuity. Mass transfer modeling is provided for the phase change associated with sheet cavitation. Using quasi-3D (Q3D) analysis, steady and time-dependent analyses were performed across a wide r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
61
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(70 citation statements)
references
References 5 publications
2
61
0
2
Order By: Relevance
“…(13) we obtain If the correction angles at the inlet (a′ 5 i , β 1 ) and the outlet (a′ 5 f , β 2 ) regions are known, the coefficient C 1 , C 2 , C 3 and C 4 in Eq. (10) could easily be found as follows: (15) In this study, the correction angle is a key factor to construct three-dimensional impeller geometry by curve fitting of hub-shroud contours. It is found that the inlet angle and outlet angle defined in the velocity triangle correspond to the first derivative of cubic spline function.…”
Section: Construction Of Impeller Geometrymentioning
confidence: 99%
See 1 more Smart Citation
“…(13) we obtain If the correction angles at the inlet (a′ 5 i , β 1 ) and the outlet (a′ 5 f , β 2 ) regions are known, the coefficient C 1 , C 2 , C 3 and C 4 in Eq. (10) could easily be found as follows: (15) In this study, the correction angle is a key factor to construct three-dimensional impeller geometry by curve fitting of hub-shroud contours. It is found that the inlet angle and outlet angle defined in the velocity triangle correspond to the first derivative of cubic spline function.…”
Section: Construction Of Impeller Geometrymentioning
confidence: 99%
“…Some phenomena, such as flow separation and cavitation shown by Pak and Lee (1998), have great effects on the loss of pressure head inside the passage. Medvitz et al (2002) performed study for a better understanding of the physics of cavitation and presented multiphase CFD findings for centrifugal pump analysis. Byskov and Jacobsen (2003) generated a model for centrifugal impeller at design and offdesign conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to study the internal cavitating flow in a centrifugal pump. Medvitz et al [1] analyzed centrifugal pump performance under developed cavitating conditions by a multi-phase CFD method. The mixture momentum and volume continuity equations are solved along with vapor volume fraction continuity.…”
Section: Introductionmentioning
confidence: 99%
“…The service life of the pumps is then reduced greatly [1,2]. Due to the importance of the cavitation phenomenon and the great process in the cavitation and turbulence models, numerical simulations have been widely used to investigate the cavitation flow field in the pumps [3][4][5][6].…”
mentioning
confidence: 99%
“…By using the cavitation model proposed by Kunz et al [7], Medvitz et al [3] calculated the cavitating flow in a centrifugal pump at small cavitation numbers. They analysed the reason why the pump head drops at small cavitation numbers for the off-designed condition, but the assumption of the potential flow in their calculations limits their methods used in more application.…”
mentioning
confidence: 99%